Coffins on our shoulders : the experience of the Palestinian citizens of Israel - Rabinowitz, Dan, 1954- (University of California Press, 2005)
This highly original historical and political analysis of the Arab-Israeli conflict combines the unique perspectives of two prominent segments of the Middle Eastern puzzle: Israeli Jews and the Palestinian citizens of Israel. Written jointly by an Israeli anthropologist and a Palestinian family therapist born weeks apart to two families from Haifa, Coffins on Our Shoulders merges the personal and the political as it explores the various stages of the conflict, from the 1920s to the present.